DFT Study on the Janus ZrSSe Monolayer for Its Potential Application in NO Gas Sensing - Zhang, Mengyang (Langmuir : the ACS journal of surfaces and colloids, 2024)
The growth of industry has resulted in increased global air pollution, necessitating the urgent development of highly sensitive gas detectors. In this work, the adsorption of the Janus ZrSSe monolayer for CO, CO2, NH3, NO, NO2, and O2 was studied by first-principles calculations. First, the stability of the ZrSSe monolayer is confirmed through calculations of cohesive energy and AIMD simulations. Furthermore, the calculations indicate that the Se layer exhibits higher selectivity and sensitivity toward gas molecules compared to the S layer. Specifically, among the gases adsorbed on the Se layer, NO has the shortest adsorption distance (1.804 Å), the lowest adsorption energy (-0.424 eV), and the greatest electron transfer (0.098 e). Additionally, density of states analysis reveals that adsorption of NO, NO2, and O2 on the Janus ZrSSe monolayer can induce a transition from a nonmagnetic to a magnetic state. The adsorption of NO not only alters the magnetic state but also induces a transition from a semiconductor to metal, which is highly advantageous for gas sensing applications. There results suggest that the Janus ZrSSe monolayer has the potential to serve as a highly sensitive detector for NO gas